Intranasal oxytocin and a polymorphism in the oxytocin receptor gene are associated with human-directed social behavior in golden retriever dogs - Persson, Mia; Trottier, Agaia J.; Bélteky, Johan; Roth, Lina; Jensen, Per (Hormones and Behavior, 2017)
The oxytocin system may play an important role in dog domestication from the wolf. Dogs have evolved unique human analogue social skills enabling them to communicate and cooperate efficiently with people. Genomic differences in the region surrounding the oxytocin receptor (OXTR) gene have previously been associated with variation in doge communicative skills. Here we have utilized the unsolvable problem paradigm to investigate the effects of oxytocin and OXTR polymorphisms on human-directed contact seeking behavior in 60 golden retriever dogs. Human-oriented behavior was quantified employing a previously defined unsolvable problem paradigm. Behaviors were tested twice in a repeated, counterbalanced design, where dogs received a nasal dose of either oxytocin or saline 45 min before each test occasion. Buccal DNA was analysed for genotype on three previously identified SNP-markers associated with OXTR. The same polymorphisms were also geno-typed in 21 wolf blood samples to explore potential genomic differences between the species. Results showed that oxytocin treatment decreased physical contact seeking with the experimenter and one of the three polymorphisms was associated with degree of physical contact seeking with the owner. Dogs with the AA-genotype at this locus increased owner physical contact seeking in response to oxytocin while the opposite effect was found in GG-genotype individuals. Hence, intranasal oxytocin treatment, an OXTR polymorphism and their interaction are associated with doge human-directed social skills, which can explain previously described breed differences in oxytocin response. Genotypic variation at the studied locus was also found in wolves indicating that it was present even at the start of dog domestication. Funding Agencies|European Research Council (ERC) [322206]